Crashworthiness of lantern-like lattice structures with a bidirectional gradient distribution. (15th December 2022) - Liang, Hongyu; Sun, Bohua; Hao, Wenqian; Sun, Hao; Pu, Yongfeng; Ma, Fangwu
Highlights: The novel structure with a bidirectional gradient distribution is proposed. The longitudinal gradient design can increase the energy absorption. The lateral gradient design can enhance the stability of crashworthiness. Equal gradient layer design shows excellent energy absorption capacity. Abstract: Oblique impact loading conditions strongly influence the crashworthiness of energy-absorbing structures. In the present work, inspired by the distribution characteristics of spider webs, a bidirectional gradient configuration of cell wall thickness was introduced to enhance the crashworthiness of lattice structures based on the functional similarity of longitudinal gradient distribution and lateral gradient distribution. A comparative study of different gradient configurations was carried out using the finite element (FE) simulations. It was found that the longitudinal gradient distribution was beneficial to improve the comprehensive energy absorption capacity of the lattice structure, especially under small-angle impact conditions. With the increase of impact angle, the effect of the lateral gradient distribution on the stability of energy absorption became more prominent. In comparison to the uniform structure and the single gradient structure, the lattice structure with the positive longitudinal gradient and the negative lateral gradient distribution exhibited great potential in enhancing the energy absorption capacity and reducing the peak crushing force. A detailed parametric study was executed to explore the effects of the gradient layer number and the gradient thickness increment of the bidirectional gradient distribution on the comprehensive energy absorption capacity and energy absorption stability of the structure under multi-angle impact conditions. The findings of this research provide valuable guidelines to design bio-inspired lattice structures subjected to complex loading conditions. Graphical abstract: Image, graphical abstract